Five-Tier Diagnostic Test Instrument Validation on Reaction Rate Materials: To Identify the Causes of Misconception and Student Representation - Deni Ainur Rokhim; Hayuni Retno Widarti; Sutrisno Sutrisno (Postgraduate, University of Mataram, 2023)
This study aims to determine the validity of the five-tier diagnostic instrument. Empirical validation tests were carried out to identify the items' difficulty level, the different power of the items, the percentage of distractor effectiveness, and test the validity and reliability of the items. The results show that the five-tier diagnostic test instrument is feasible and valid to use by looking at the test difficulty level, discriminating power, distractor effectiveness, item validity, empirical validity, and reliability test. The difficulty level of the questions is included in the average level of easy difficulty at Tier A and Tier R. In contrast, and the Multiple representatives are included in the medium level of difficulty. The average results at Tier A, Tier R, and Multiple Representative in the differential power test have sufficient differential power.